Pengaruh Model Pembelajaran Kooperatif Tipe STAD Terhadap Peningkatan Hasil Belajar Siswa Kelas V Sekolah Dasar - Ecep Suriat (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This research was motivated by the low learning outcomes of students in class V of State Elementary School in Sukabumi City. This is because the teacher does not explain the direction of small group learning, the proportion of tasks is evenly distributed to each group member, and motivates students to cooperate with their groupmates. The ability to work together in the classroom can foster interpersonal skills. The goal of the study was to develop collaborative skills using the conference approach of elementary school fifth graders. This research method uses class action research. In research, data collection techniques use observation sheets, location records, and documentation. The subjects of this study were 35 V-graders from elementary school. Data processing and data analysis used are qualitative data analysis and quantitative data analysis. Student learning outcomes increased by 40% from 28.57% in pre-cycle learning to 68.57% in cycle 1, so the final results obtained met the criteria for study success. Thus, research shows that applying a conference approach is able to improve student learning outcomes through learning activities with a conference approach.